Plasmonic magnesium nanoparticles decorated with palladium catalyze thermal and light-driven hydrogenation of acetylene. Issue 16 (29th March 2023) - Lomonosov, Vladimir; Wayman, Thomas M. R.; Hopper, Elizabeth R.; Ivanov, Yurii P.; Divitini, Giorgio; Ringe, Emilie
Abstract : Plasmonic Mg cores capture light to decrease the activation energy and increase the rate of acetylene hydrogenation on Pd nanoparticles. Abstract : Bimetallic Pd–Mg nanoparticles were synthesized by partial galvanic replacement of plasmonic Mg nanoparticles, and their catalytic and photocatalytic properties in selective hydrogenation of acetylene have been investigated. Electron probe studies confirm that the Mg–Pd structures mainly consist of metallic Mg and sustain several localized plasmon resonances across a broad wavelength range. We demonstrate that, even without light excitation, the Pd–Mg nanostructures exhibit an excellent catalytic activity with selectivity to ethylene of 55% at 100% acetylene conversion achieved at 60 °C. With laser excitation at room temperature over a range of intensities and wavelengths, the initial reaction rate increased up to 40 times with respect to dark conditions and a 2-fold decrease of the apparent activation energy was observed. A significant wavelength-dependent change in hydrogenation kinetics strongly supports a catalytic behavior affected by plasmon excitation. This report of coupling between Mg's plasmonic and Pd's catalytic properties paves the way for sustainable catalytic structures for challenging, industrially relevant selective hydrogenation processes.